LiF-MO (M=Co, Fe, Ni) Nanocomposite Thin Film as Anode Materials for Lithium-ion Battery - Wenyuan Liu; Changfeng Ke; Xuehai Yan; Li Duan; Lin Li; Chong Liu (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2015)
To investigate the electrochemical performance of MO (M=Co, Fe, Ni) nanostructures on lithium insertion and extraction, size-controlled LiF-MO nanocomposite thin-film electrodes, consisting of metallic M and M oxide (MO) nanoparticles in an amorphous, inert LiF matrix, were designed and fabricated using a RF sputtering system with metallic M and LiF mixture targets. The structural and electrochemical properties of nanocomposite thin-film electrodes were characterized using TEM, SAED, XRD, XPS, and electrochemical measurements. The results showed that MO particles with average particle sizes of ca.10nm were well-dispersed in LiF matrix to form a kind of homogeneous LiF-MO nanocomposite by the sputtering method. The inert medium of LiF provides an effective matrix to prevent the crystallization and agglomeration of MO during the deposition and electrochemical cycling of the thin film electrode, and then the well-formed nanophase structure in the nanocomposite thin-film electrodes leads to an excellent electrochemical cycling performance with the stable discharge specific capacity above 300mAh/g.